ANALISIS PERAN ORANG TUA TERHADAP KEMATANGAN EMOSI ANAK USIA 3–4 TAHUN DI PPT MUTIARA BUNDA - Handajani, Handajani; Abidin, Ratno; Sa’ida, Naili; Gusmaniarti, Gusmaniarti (STKIP Pesisir Selatan, 2025)
Emotional maturity in early childhood is an important foundation for social, cognitive, and moral development. This study aims to analyze the relationship between parental roles in emotional regulation and the level of emotional maturity of children aged 3–4 years at the Mutiara Bunda PPT. The study used a quantitative correlational approach with instruments in the form of a parental emotional regulation scale adapted from Gross's (2023) theory and a child social-emotional development scale developed by Solihah et al. (2022). The results of validity and reliability tests indicate that both instruments have high content validity and excellent reliability (Cronbach's α > 0.9). The results of the Pearson correlation analysis showed a significant positive relationship (r = 0.65, p < 0.01) between parental emotional regulation and children's emotional maturity. The dimensions of cognitive strategies and attention diversion showed the highest contribution to children's emotional regulation. This study emphasizes the importance of parents' active role in developing emotional regulation as a foundation for children's emotional maturity. The practical implications of this study point to the need for parenting and training programs that focus on emotional management in early childhood care.